256 Detection of NCOA2/3 gene fusions in uterine tumors resembling ovarian sex cord tumors (UTROSCT). (18th September 2019) - Pinto, A; Lastra, RR; Ritterhouse, LL; Segal, J; Krausz, T; Bennett, JA
Abstract : Objectives: Uterine tumors resembling ovarian sex cord tumors (UTROSCT) are rare mesenchymal neoplasms of uncertain histogenesis that are challenging to diagnose due to their morphological and immunohistochemical overlap with more conventional entities. While DNA sequencing has failed to identify recurring mutations in these tumors, RNA sequencing recently detected NCOA2/3 fusions in two small series. The objective of this study was to further describe the characteristics of two UTROSCTs. Methods: We retrospectively evaluated the clinicopathological and immunohistochemical features of two UTROSCTs, and performed RNA sequencing to detect gene fusions. Results: The patients were 52 and 57 years old, tumors measured 5 and 12 cm, and were confined to the myometrium. Both showed multiple histologic patterns including diffuse, cord-like, and trabecular, with rhabdoid cells focally present. One UTROSCT had significant cytologic atypia and brisk mitotic activity, but both lacked necrosis and lymphovascular invasion. Variable immunohistochemical expression for calretinin, inhibin, WT-1, ER, CD10, and pankeratin was noted. RNA sequencing detected an ESR1-NCOA3 fusion in one tumor, whereas the other had a GREB1-NCOA2 rearrangement. The former patient is alive and well five months after diagnosis, while the latter recurred two years later, and is currently alive with disease (six years after original diagnosis). Conclusions: The detection of NCOA2/3 fusions in two additional UTROSCTs further supports this rearrangement as a characteristic finding in these rare tumors. Additional studies are warranted to determine its sensitivity and specificity in UTROSCTs compared to other gynecologic neoplasms.